Utilization of Palm Kernel Ash and Shell as Sustainable Binders and Aggregates for Structural Block Production - Clement Nworji Obiora; Oladapo Babafemi Fakiyesi; Chukwunakueze Arinze Nwekeoti (Journal Majelis Paspama, 2025)
In order to develop a block for structural purposes, this study investigates the use of Palm Kernel (PK) ash and sodium silicate as a binder to produce a six-inch block. The disposal of PK ash and shell, which are agricultural waste products from palm oil mills, is a hazard for the environment. The PK ash possesses pozzolanic qualities that make it possible to partially substitute cement and also play a significant role in the strength and durability of concrete. By using PK ash in concrete, the growing issues of cement scarcity and high cost will be lessened. Three different varieties of PK ash were created at various temperatures (350-7500 C) and used to replace up to 50% PC in order to explore the PK ash's ability to replace PC. In order to research the aggregate replacement potential of the PK shell, up to 100% of the coarse aggregate was replaced.